Households' access to financial services some evidence from survey data - Llanto, Gilberto M. ([Quezon City] School of Economics, University of the Philippines, 2015)
Many studies look at financial inclusion from the supply side. The discussion in those studies revolves around the different types of financial services being developed to provide the excluded segment of the population with access to such services and the evolving regulatory frameworks supporting those innovative financial services. This paper views financial inclusion from the perspective of households who use financial services and asks what factors determine access to financial services. It provides a quantitative estimation of the factors affecting household decision to participate in the formal financial markets and the impact of the utilization of financial services on household incomes. It uses micro-data from the Annual Poverty Indicators Survey in the estimation. The empirical findings provide useful information for designing policies and interventions to foster inclusive finance. It points to financial education of households as a key intervention in financial inclusion strategies.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 189-190)
Keywords: Discrimination in financial services -- Philippines; Financial services industry -- Philippines; Financial exclusion -- Philippines